Inducible immunity with a pilus preparation booster vaccination in an animal model of Haemophilus ducreyi infection and disease. - Desjardins, M (1995)
Using the temperature-dependent rabbit model of Haemophilus ducreyi infection as a quantitative virulence assay, we tested the abilities of two bacterial antigen preparations to induce protection against subsequent infection and disease. Lipooligosaccharide (LOS) and a pilus preparation were purified from H. ducreyi 35000 and were used in a booster immunization procedure. The serologic response to each immunogen was monitored by enzyme immunoassay. H. ducreyi virulence was assayed by intraepithelial inoculation and subsequent measurement of disease for homologous strain 35000 or clinical isolate RO-34. LOS and the pilus preparation induced humoral responses. The kinetics of the LOS antibody response suggest a type 1 T-independent response, whereas the pilus preparation induced an anamnestic response. An inoculum of 10(5) CFU of H. ducreyi 35000 or RO-34 consistently produced ulcerative chancroidal lesions in naive rabbit controls. Immunization with LOS did not modify the virulence of H. ducreyi 35000. Immunization with the strain 35000 pilus preparation significantly reduced the severity of disease and the duration of infection and disease compared with controls, with either homologous or heterologous strain infection. The histology of lesions from pilus preparation-vaccinated rabbits compared with that of lesions from controls revealed accelerated lymphoid cell recruitment, more prominent plasma cell infiltrate, and reduction in subsequent histiocytic infiltration. We conclude that both LOS and the pilus preparation are immunogenic and that the latter induces homologous and heterologous strain protection in this animal model of infection and disease.